Streptococcus gallolyticus Bacteremia Detected in Apheresis Platelets and Its Link to Colonic Neoplasms - Lemanski, Francisco Costa Beber; Barp, Anna Laura Duro; Hammacher, Gabriela Kohl; Cas, Martina Estacia Da; Wink, Cristine Moratelli; Voloski, Ana Paula dos Santos; Pasqualotti, Adriano; Araújo, Cristiane da Silva Rodrigues de (Journal of Coloproctology, 2022)
Introduction Streptococcus gallolyticus belongs to the Streptococcus bovis complex, and it is a common bacterium colonizing the gastrointestinal tract. Its presence in the blood may suggest an underlying pathology such as a colonic neoplasm. We report herein a case of S. bovis bacteremia in an apheresis platelet donor, review similar cases in the literature, and suggest a flowchart for the management of similar cases in other blood donation centers.Case Presentation A 61-year-old subject presented to a Hemotherapy Service to make an apheresis platelet donation. On quality control testing, S. gallolyticus was identified in hemoculture, and the donor was called back for follow-up. At first, a new hemoculture was requested, and the patient was referred to the outpatient department of infectious diseases to further investigate pathologies associated with S. gallolyticus. A subsequent colonoscopy investigation evidenced a polypoid structure in the ascending colon. Pathology reported the resected specimen as a low-grade tubular adenoma.Conclusion Isolation of S. bovis in blood products requires further investigation and should be managed with precision by Hemotherapy Services. A standard protocol for the management of asymptomatic patients with S. bovis positive hemoculture, with the requests of a new blood culture, a colonoscopy, and an echocardiogram is crucial, as it may ensure early diagnosis and reduce morbidity and mortality.
Keywords: Streptococcus gallolyticus; Streptococcus bovis; colonic neoplasm; colorectal cancer; apheresis